Analysis of Consumer Perception of Interest in Organic Vegetables in North Sumatra (Case Study: Semangat Village, Karo Regency) - Habibie, Dian; Arumugam, Nalini; Mohd Suhaimi, Nurul Aisyah Binti; Handayani, Leni; Wahyuni, Sri (Westscience Press, 2025)
This article analyzes consumer perceptions and interest in organic vegetables in Semangat Village, Karo Regency, North Sumatra. Given the growing popularity of organic vegetables grown without synthetic pesticides and chemical fertilizers, this study aims to identify factors influencing consumer purchasing interest. Data were collected through surveys and statistical analysis. Results indicate that while awareness of the benefits of organic vegetables is increasing, consumer purchasing interest remains low, driven by higher prices and a lack of knowledge about their benefits. This study provides insights for producers and marketers to develop effective marketing strategies and encourages increased farmer education on good organic farming practices. Emphasis is also placed on the need for transparency and education to increase consumer trust.